Tadalafil combined with remote ischemic preconditioning in the prevention of renal ischemia/reperfusion injury - Azevedo, Italo Medeiros; Vieira da Silva, Gabriela; Sinara Varela Constantino de Medeiros, Aristela; Sibelle Varela Constantino de Medeiros Dumaresq de Souza, Ariadne; Karla Aires de Macêdo, Rosana; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2018)
PURPOSE: This study aimed to evaluate whether the combination of tadalafil treatment and remote ischemic preconditioning may provide protection against ischemia reperfusion injury (I/R) in kidneys of rats. METHODS: Twenty-four male Wistar rats weighing 280-300g were randomly divided into 3 groups: Group 1 - (control), only right nephrectomy was performed. No treatment with tadalafil. Group II - Left renal ischemia, right nephrectomy, without remote preconditioning, treatment with tadalafil (1.0 mg/kg, oral). Group III - Left renal ischemia, right nephrectomy, with remote preconditioning, treatment with tadalafil. RESULTS: 24 h after, urea and creatinine dosage and histopathology of the ischemic kidneys were performed. In the left kidney of control group rats, a higher degree of cellular necrosis was observed when compared to the tadalafil group, with and without remote preconditioning. On the preconditioning + tadalafil group rats, there was a significant reduction in histological parameters when compared to the Ischemia + tadalafil group rats (p<0.05). In group III, comparing to other groups, a significant improvement of the left kidney function was observed, through the lower values ??of the urea and creatinine dosages. CONCLUSION: This study demonstrated protective effects of remote preconditioning + tadalafil in an experimental model of renal I/R in the rat. The results demonstrated that a single dose of tadalafil prior to renal I/R attenuated the histopathological lesions, especially cellular necrosis, and renal function tests.